A three-dimensional CFD simulation of corium jet breakup in intensive vapor generation condition - Jeong-Hyun Eom; Ji-Won Choi; Gi-Young Tak; In-Sik Ra; Huu Tiep Nguyen; Hae-Yong Jeong (Nuclear Engineering and Technology)
The complexity of ex-vessel phenomena during a severe accident limits the most previous CFD applications only to hydrodynamic aspects. The present study performs numerical analysis of jet breakup and debris bed formation under intensive steam generation using the STAR-CCM + code. The CFD prediction of the MATE06 experiment demonstrates jet breakup progression patterns consistent to the experiment results. The predicted jet breakup lengths are in good agreement with the MATE 06 data in earlier stage. However, some disparities of the leading-edge position between the MATE 06 and the simulation are predicted in late stage. This is attributed to non-periodic repetitions of the detachment and reattachment of some fragmented segments to the jet column. The difference of frictional force or shear stress between the experiment and CFD simulation also causes uncertainty in the amount of steam generation. In overall, the present study becomes significant to simulate successfully the series of jet breakup process and debris bed formation under intensive steam generation condition. In future studies, it is required to upgrade the current model through more evaluation of experiments and to develop much sophisticated models which provide an enhanced realistic simulation of ex-vessel phenomena.